The use of dose-escalated radiation for locally advanced non-small cell lung cancer in the U.S., 2004–2013. Issue 1 (December 2017) - Christodouleas, John; Hall, Matthew; van der Pas, Marjorie; Guo, Wensheng; Schultheiss, Timothy; Gabriel, Peter
Abstract Purpose/Objectives The clinical effects of radiation dose-intensification in locally advanced non-small cell lung (NSCLCa) and other cancers are challenging to predict and are ideally studied in randomized trials. The purpose of this study was to assess the use of dose-escalated radiation for locally advanced NSCLCa in the U.S., 2004–2013, a period in which there were no published level 1 studies on dose-escalation. Materials/Methods We performed analyses on two cancer registry databases with complementary strengths and weaknesses: the National Oncology Data Alliance (NODA) 2004–2013 and the National Cancer Database (NCDB) 2004–2012. We classified locally advanced patients according to the use of dose-escalation (>70 Gy). We used adjusted logistic regression to assess the association of year of treatment with dose-escalated radiation use in two periods representing time before and after the closure of a cooperative group trial (RTOG 0617) on dose-escalation: 2004–2010 and 2010–2013. To determine the year in which a significant change in dose could have been detected had dose been prospectively monitored within the NODA network, we compared the average annual radiation dose per year with the forecasted dose (average of the prior 3 years) adjusted for patient age and comorbidities. Results Within both the NODA and NCDB, use of dose-escalation increased from 2004 to 2010 (p < 0.0001) and decreased from 2010 to 2013 (p = 0.0018), even after controlling for potential confounders. Had the NODA network been monitoring radiation dose in this cohort, significant changes in average annual dose would have been detected at the end of 2008 and 2012. Conclusions Patterns of radiation dosing in locally advanced NSCLCa changed in the U.S. in the absence of level 1 evidence. Monitoring radiation dose is feasible using an existing national cancer registry data collection infrastructure.